At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
You need to get each variable on separate sides
What did you get as an answer?
I got 4, -5. But my sister said it was wrong.
do you have your work? We can possibly see what you did wrong. :) the answer is wrong, but it doesnt seem too far off
No I erased it all.
hmm... okay well, we can solve this with a few techniques. I think its set up nicely for elimination (there's a y and a -y which will cancel), so we can just add the equations together.
Can you show me how you would do it?
|dw:1333053747989:dw| its not a great notation, but i think you can see what's going on -- adding together the terms on each side to eliminate a variable
then divide by 3, so x=4 We would substitute this back into x-y=10 or 2x+y=2 4-y=10 2(4) + y = 2 -y=6 8 + y = 2 y=-6 y = -6
Oh I get it now I think.
Well, if there's anything you are unsure of, I'll try to explain better. :)
so x = 12? Do I simplify it down to 4?
i left off on the drawing not completely simplified, but this is what i did next since it was "3x = 12": |dw:1333054190702:dw|
Can you help me with another problem?
"For the following system, if you isolated x in the first equation to use the Substitution Method, what expression would you substitute into the second equation? -x + 2y = -6 3x + y = 8"
I got '-2y + 6' - I don't know how. And I think it's wrong.
So, we'd substitute whatever the x-value is when we isolate it. -x + 2y = -6 -x + 2y - 2y = -6 - 2y -x = -6 - 2y (-1)(-x) = (-1)(-6 - 2y) x = -1*-6 + -1*-2y (distributing -1 0 = 6 + 2y
Thank you so much :)
You're welcome. :D Glad to help!
im thinking that you may just be multiplying one thing on the other side by -1 to get "-2y + 6" instead of the whole expression, which is something to avoid